2012
DOI: 10.1038/nnano.2012.170
|View full text |Cite
|
Sign up to set email alerts
|

In situ atomic-scale imaging of electrochemical lithiation in silicon

Abstract: In lithium-ion batteries, the electrochemical reaction between the electrodes and lithium is a critical process that controls the capacity, cyclability and reliability of the battery. Despite intensive study, the atomistic mechanism of the electrochemical reactions occurring in these solid-state electrodes remains unclear. Here, we show that in situ transmission electron microscopy can be used to study the dynamic lithiation process of single-crystal silicon with atomic resolution. We observe a sharp interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
617
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(669 citation statements)
references
References 30 publications
47
617
5
Order By: Relevance
“…In recent years, the in situ TEM electrochemical testing technique has been used to probe structural variations of nanoscale electrode materials with high spatial resolution during discharge/charge 36, 37, 38, 39, 40, 41, 42, 43, 44, 45. We also constructed an electrochemical nanodevice using an Fe‐S@CNT as a working electrode for an in situ TEM experiment to examine its structural changes and to obtain direct insight into its Li‐storage mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the in situ TEM electrochemical testing technique has been used to probe structural variations of nanoscale electrode materials with high spatial resolution during discharge/charge 36, 37, 38, 39, 40, 41, 42, 43, 44, 45. We also constructed an electrochemical nanodevice using an Fe‐S@CNT as a working electrode for an in situ TEM experiment to examine its structural changes and to obtain direct insight into its Li‐storage mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The lithiation process during electrochemical cycling for several electrode materials has been studied using this configuration. [56][57][58][59] Although intercalation materials were also studied, alloying and conversion anode materials have been more frequently studied because the large volume change that is associated with the charge/discharge can be readily detectable even under low magnifications. Liu et al 60 reported the direct observation of anisotropic swelling of Si nanowires during lithiation, and a following study further revealed electrochemical-induced fractures on the nanostructured Si that had different particle sizes.…”
Section: Open-cell Configurationmentioning
confidence: 99%
“…Liu et al 60 reported the direct observation of anisotropic swelling of Si nanowires during lithiation, and a following study further revealed electrochemical-induced fractures on the nanostructured Si that had different particle sizes. 56 The lithiation process was observed at the atomic scale, which led to the discovery of a layer-by-layer peeling mechanism for the lithiation on Si {111} facets, 57 and it explained the orientation-dependent Li mobility in Si. Wang et al 58 studied the lithiation mechanism of amorphous SnO 2 nanowires and observed a simultaneous partitioning and coarsening characteristic of Li x Sn as a result of Sn and Li diffusion.…”
Section: Open-cell Configurationmentioning
confidence: 99%
“…Furthermore, Lee et al [26] demonstrated anisotropic deformation of silicon nanopillars during lithitation. A number of first-principles calculations and experimental studies have shown that the lithiation reaction is anisotropic and fastest in the <110> direction [26][27][28][29]. If lithiation is controlled by this reaction mechanism as opposed to diffusion through the lithiated phase, anisotropic expansion may occur [29,30].…”
Section: Introductionmentioning
confidence: 99%